A fuzzy‐based multi‐objective robust optimization model for a regional hybrid energy system considering uncertainty. Issue 4 (11th March 2020) - Song, Xueying; Zhao, Rui; De, Gejirifu; Wu, Jing; Shen, Huayu; Tan, Zhongfu; Liu, Jicheng
Abstract: Regional hybrid energy system (RHES) is an effective way to accommodate clean energy and reduce its uncertainty. It is also an important development direction for energy market reform, playing an important role in the field of energy supply and demand. Based on electricity price, thermal price, and the relationship between load supply and demand, the paper proposes an optimal scheduling model for regional energy systems to promote clean energy consumption. Firstly, the typical structure and system modules of the integrated regional energy system are introduced in detail, and the two subsystem operating models of electricity and heating are given. Secondly, a multi‐objective function that combines the economics and stability of the system is constructed. The model maximizes the economic benefits and minimizes the net load fluctuations on the basis of maximizing the consumption of clean energy. The multi‐objective singularity is realized by fuzzy membership function. The decision‐making risk caused by the uncertainty of clean energy output is analyzed by introducing robust optimization theory. Finally, the effectiveness of the proposed model is verified based on a region in northwestern China. The results show that the proposed multi‐objective model can combine different optimization demands together, maximize the economic characteristics of clean energy while properly controlling risks, and provide reasonable support for decision makers to develop optimal operation plans. Abstract : Regional energy system is an effective way to accommodate clean energy and reduce its uncertainty. Based on electricity price, thermal price, and the relationship of load supply and demand, the paper proposes an optimal scheduling model for regional energy systems to promote clean energy consumption.